Attachment and Therapeutic Alliance in Substance Use Disorders: Initial Findings for Treatment in the Therapeutic Community - Rübig, Leonie L.; Fuchshuber, Jürgen; Köldorfer, Pia; Rinner, Anita; Fink, Andreas; Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2021)
Background: There is convincing evidence that individuals suffering from Substance Use Disorder (SUD) often present insecure attachment patterns. In contrast, a strong therapeutic alliance in treatment of SUD has been found to lead to a more positive treatment outcome. However, insecure attachment has been observed to be linked with weaker therapeutic alliance strength. The primary aim of this explorative study was to gain initial insights regarding the influence of attachment and personality characteristics on therapeutic alliance and therapy motivation in SUD patients undergoing treatment at a therapeutic community. Furthermore, SUD patients were compared to healthy controls regarding attachment, personality and mood pathology. Methods: A total sample of 68 participants, 34 inpatients in SUD treatment and 34 age-gender and education adjusted controls, were investigated. Both groups filled in the Adult Attachment Scale (AAS), the Inventory of Personality Organization (IPO-16), and the Brief Symptom Inventory (BSI-18) questionnaires. Additionally, SUD patients filled in the Working Alliance Inventory (WAI-SR) and the adapted German version of the University of Rhode Island Change Assessment scale (FEVER). Results: In line with our assumptions, SUD patients exhibited a decreased amount of attachment security (AAS) which was related to higher personality (IPO-16) and mood pathology (BSI-18). Furthermore, correlational analysis revealed the WAI-SR dimension Bond being positively associated with more secure attachment. A strong task alliance was linked to the Action stage of change (FEVER) and decreased mood but not personality pathology. Conclusion: Our findings confirm the putative negative effect of attachment and personality pathology on therapy motivation and therapeutic alliance in addiction therapy as well as more specifically in therapeutic community treatment. Future research in enhanced samples might focus more on the long-term effects of the interaction of attachment, personality and therapeutic alliance variables.